Impaired default mode network along with increased functional connectivity of the medial temporal lobe as a function of CSF p‐Tau/Ab42 ratio in cognitively unimpaired individuals. (December 2021) - González‐de‐Echávarri, José María; Milà‐Alomà, Marta; Operto, Greg; Falcon, Carles; Minguillón, Carolina; Fauria, Karine; Simon, Maryline; Kollmorgen, Gwendlyn; Molinuevo, Jose Luis; Zetterberg, Henrik; Blennow, Kaj; Suarez‐Calvet, Marc; et al.
Abstract: Background: Amyloid‐b (Ab) and tau exert a synergistic action on brain structure and function in cognitively unimpaired (CU) individuals. However, these two biomarkers have so far been investigated separately. Recently, it was proposed that the cerebrospinal fluid (CSF) phospho‐tau (pTau)/Ab42 ratio may represent a novel prognostic core biomarker, providing information on both proteinopathies along the preclinical Alzheimer's disease (AD) continuum . Here, we aim to characterize the association between CSF pTau/Ab42 and resting‐state functional connectivity (FC), an established imaging marker of AD, in CU individuals. Method: We included 349 CU participants from the ALFA study (mean age=60.21 years) who underwent deep phenotype screening, including CSF data collection and resting‐state functional magnetic resonance imaging (fMRI). CSF Ab42 was assessed with the exploratory Roche NeuroToolKit arobust prototype assays, while pTau181 was measured with the Elecsys® Phospho‐Tau (181P) CSF immunoassay (Roche Diagnostics International Ltd). The CONN toolbox was used to preprocess and analyze the fMRI data. fMRI volumes were parceled into 218 regions and bivariate correlations in the filtered fMRI signal among parcels were computed. A linear regression model was used to assess the impact of continuous pTau/Ab42 ratio on FC, adjusting for age, sex, years of education and APOE ‐e4 status. A threshold of uncorrected p<0.005 using non‐parametric pair‐wise clustering was implemented. Result: Higher pTau/Ab42 ratio were associated with decreased FC within the default mode network (DMN) (Fig. 1), but increased FC within the temporo‐hippocampal (THN) and visual networks (VN) (Fig. 2). Also, we observed a reduced FC between the sensorimotor network and both the DMN and THN, as a function of pTau/Ab42 levels (Fig. 2). Conclusion: Our results suggest that individuals with more advanced pathology in the preclinical AD continuum, reflected by higher pTau/Ab42 ratio, present altered FC across different distributed neural systems, both within and between networks. The reduced within‐DMN connectivity resembles earlier findings of DMN disruption as a function of cerebral Ab accumulation. However, the increased FC within the THN and VM may be indicative of a compensatory strategy to sustain cognitive functions despite AD pathology. Future studies shall include measures of cognitive performance along with longitudinal assessment to clarify this aspect.